The hidden costs of being public: Evidence from multinational firms operating in an emerging market - Slutzky, Pablo (Journal of Financial Economics, 2021)
I study how firms deal with business regulations that limit their operations. I first show that the ownership structure of a firm affects its degree of compliance with regulations, with publicly listed firms complying more than privately held ones. This differential compliance imposes a burden on listed firms that helps explain mergers and acquisitions patterns. When regulatory levels increase, private firms acquire listed ones and listed firms stop acquiring private ones. These results uncover an additional cost faced by listed companies, identify a new driver of M&A transactions, and show that high levels of regulation lead to opaque corporate structures.